Sclerema Neonatorum in a Full-Term Infant Showing Favorable Prognosis - Park, Seh Hyun (Ann Dermatol, 2017)
Sclerema neonatorum (SN) is a rare disease characterized by firm, indurated, waxy skin lesions extending throughout the body, sparing the fat-free soles, palms, and genitalia. The prognosis of SN is generally very poor, with a high fatality rate. We report the case of a full-term infant with delayed onset of SN showing good prognosis. A 4-month-old Korean male infant presented with diffuse waxy, sclerotic skin lesions on the whole body, sparing the face, nipples, and genital area, which began developing at 2 months of age. Histopathologic findings of the sclerotic skin lesions showed wide, fibrous intersecting bands in the subcutaneous fat tissue. Only sparse infiltration of lymphocytes and histiocytes was observed in the fat lobules and septa. Based on clinical presentation and histopathologic findings, he was diagnosed with SN. The patient survived with conservative care and had mild improvement of the skin lesions on his follow-up visit at 12 months of age.